Utilization of library resources and services in Uganda - Uwiringiye Winnie (Uganda Christian University, 2024)
ABSTRACT This study analyzes the relationship between library resources and academic performance in universities, drawing on an investigation of factors that influence students' usage of, and barriers to using, library resources. Library resources, both physical and digital, are foundational in promoting academic excellence through access to information, study materials, and research support. These resources are utilized when one considers the facilitative factors of accessibility, user awareness, availability of the digital platform, and relevance of materials to the academic requirements of the students. On the contrary, there are some barriers that make students fail to utilize them; these include but are not limited to limited access of the digital resources, restrictive hours of operation in the libraries, fewer study areas, and lack of knowledge in accessing library systems. The results of this study demonstrate the extent to which libraries are instrumental in facilitating the academic excellence of university students. However, the challenges highlighted depict how libraries should be changing their respective services in order to meet the desires and needs of the clientele. Libraries can greatly increase the usage rates and, in turn, the academic performance of students by developing digital access, altering rules of operation, and encouraging student participation. Furthermore, the study postulates that when the resources become more attuned to the needs of these diverse groups, including part-time students and those with disabilities, equity of access will be established. In this way, the libraries would ensure that full utilization of, and access to, its resources are extended to the whole campus community, hence enriching student academic life comprehensively